Mitochondrial ROS and base excision repair steps leading to DNA nick formation drive ultraviolet induced-NETosis - Azzouz, Dhia; Palaniyar, Nades (Frontiers in Immunology, 2023)
Reactive oxygen species (ROS) is essential for neutrophil extracellular trap formation (NETosis), and generated either by NADPH oxidases (e.g., during infections) or mitochondria (e.g., sterile injury) in neutrophils. We recently showed that ultraviolet (UV) radiation, a sterile injury-inducing agent, dose-dependently induced mitochondrial ROS generation, and increasing levels of ROS shifted the neutrophil death from apoptosis to NETosis. Nevertheless, how ROS executes UV-induced NETosis is unknown. In this study, we first confirmed that UV doses used in our experiments generated mitochondrial ROS, and the inhibition of mitochondrial ROS suppressed NETosis (Mitosox, SYTOX, immunocytochemistry, imaging). Next, we showed that UV irradiation extensively oxidized DNA, by confocal imaging of 8-oxyguanine (8-oxoG) in NETs. Immunofluorescence microscopy further showed that a DNA repair protein, proliferating cell nuclear antigen, was widely distributed throughout the DNA, indicating that the DNA repair machinery was active throughout the genome during UV-induced NETosis. Inhibition of specific steps of base excision repair (BER) pathway showed that steps leading up to DNA nick formation, but not the later steps, suppressed UV-induced NETosis. In summary, this study shows that (i) high levels of mitochondrial ROS produced following UV irradiation induces extensive oxidative DNA damage, and (ii) early steps of the BER pathway leading to DNA nicking results in chromatin decondensation and NETosis. Collectively, these findings reveal how ROS induces NOX-independent NETosis, and also a novel biological mechanism for UV irradiation- and -mitochondrial ROS-mediated NETosis.